2020
DOI: 10.1097/aud.0000000000000932
|View full text |Cite
|
Sign up to set email alerts
|

Frameworks for Change in Hearing Research: Valuing Qualitative Methods in the Real World

Abstract: In this article, we examine ecological validity in hearing science from a qualitative methodological perspective. We present an overview of qualitative methods, presenting their key characteristics and contrasting these techniques with quantitative approaches to enquiry. We argue that ecological validity sits at the heart of the qualitative paradigm and seek to clearly emphasize the methodological gap that could be effectively filled by qualitative or mixed methods. In doing so, we discuss qualitative methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The qualitative research used endorses a researcher's subjectivity and the “superiority of idealism, constructivism, humanism and relativism and takes into consideration the social, cultural and situational examinations of other's wellbeing, thereby enabling the incorporation of the partakers' opinions, interviews, behaviours and experiences with analysis of data for further explanation (Rapport and Braithwaite, 2018; Rapport and Hughes, 2020). Additionally, the qualitative method enables researchers to evaluate and attain rational conclusions from theoretical documentation and archives, which may also include visual data in the form of photographs, videos, maps and other visual representations, which may be challenging to carry out using the quantitative method (Rapport and Braithwaite, 2018; Rapport and Hughes, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…The qualitative research used endorses a researcher's subjectivity and the “superiority of idealism, constructivism, humanism and relativism and takes into consideration the social, cultural and situational examinations of other's wellbeing, thereby enabling the incorporation of the partakers' opinions, interviews, behaviours and experiences with analysis of data for further explanation (Rapport and Braithwaite, 2018; Rapport and Hughes, 2020). Additionally, the qualitative method enables researchers to evaluate and attain rational conclusions from theoretical documentation and archives, which may also include visual data in the form of photographs, videos, maps and other visual representations, which may be challenging to carry out using the quantitative method (Rapport and Braithwaite, 2018; Rapport and Hughes, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This work aligns with increasing calls for the use of qualitative methods in hearing research to foster ecological validity in trial findings (Keidser et al 2020;Rapport & Hughes 2020). We present qualitative findings produced from a mixed methods design, which provide an example of how qualitative data can contextualize the experience of hearing loss for a particular group.…”
Section: Discussionmentioning
confidence: 62%
“…Our study engaged a wide range of stakeholders, recognizing the multilevel socioecological influences that impact health behavior, both generally and within hearing loss in particular ( Manchaiah et al 2015 ). By using qualitative methods to document and present this regional explanatory model of hearing loss as a part of a cluster randomized trial, we are answering the call for increased ecological validity in hearing research ( Dinos et al 2018 ; Keidser et al 2020 ; Rapport & Hughes 2020 ). This work builds upon qualitative research conducted in other contexts, which has documented knowledge, attitudes, and beliefs around ear and hearing-related health care to inform health care delivery ( Curry et al 2002 ; Crandell et al 2004 ; Manchaiah et al 2015 ; Zhao et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the published literature, qualitative inquiry in hearing science has focused mainly on the social, cultural, psychological and emotional impacts of hearing loss. 49 Few qualitative studies have explored the attributes and behaviours of listening as experienced and reported by individuals with hearing loss. This review represents a novel approach to the study of listening in hearing loss.…”
Section: Discussionmentioning
confidence: 99%